Chizmachilikni o‘qitishda zamonaviy pedagogik texnologiyalarNI tatbiq etish vositalari - Esboganova, B. (SCIENCE and SOCIETY, 2023)
The article describes a method for increasing the effectiveness of the lesson and the activity of students through the use of pedagogical technologies in teaching sketching in higher education.